HLA-specific intracellular epitope processing shapes an immunodominance pattern for HLA-B*57 that is distinct from HLA-B*58:01. - Kløverpris, H; Stryhn, A; Harndahl, M; Payne, R; Towers, G; Chen, F; Riddell, L; Walker, B; Ndung'u, T; Leslie, A; Buus, S; Goulder, P (2013)
HLA-B*57 is strongly associated with immune control of HIV and delayed AIDS progression. The closely related, but less protective, HLA-B*58:01 presents similar epitopes, but HLA-B*58:01(+) individuals do not generate CD8(+) T cells targeting the KF11-Gag epitope, which has been linked to low viremia. Here we show that HLA-B*58:01 binds and presents KF11 peptide, but HIV-infected HLA-B*58:01(+) cells fail to process KF11. This unexpected finding demonstrates that immunodominance patterns can be influenced by intracellular events independent of HLA binding motifs.